'DOMINO' REACTION -IT'S PLAIN WACKY: SPORTS FINAL Edition - Bernard, Jami (Daily news (New York, N.Y. : 1920), 2005)
DOMINO. With Keira Knightley, Edgar Ramirez, Mickey Rourke, Lucy Liu, Christopher Walken, Mo'Nique, Mena Suvari. Director: Tony Scott (2:08). R: Strong violence, pervasive language, sexual content/ nudity and drug use. 1.5 Stars. The real-life story of Domino Harvey isn't pretty, although the real-life daughter of famed British actor Laurence Harvey ("The Manchurian Candidate") was once pretty enough for a brief career in modeling. "Domino," the movie, isn't pretty either - at least, not to look at - yet it airbrushes and glorifies the short, angry life of its subject in ways that are practically indecent. Director Tony Scott befriended Domino, who early on rejected the "Masterpiece Theatre" heritage of her famous father to become, of all things, a bounty hunter. Scott clearly admires the very qualities that were his friend's downfall - her fascination with all things tawdry and dangerous.